Communication Strategy of Alfamart Corporate Communication Department in Maintaining Positive Company Image - Thariq, Mighty Razzaq Ath; Priliantini, Anjang (Kalijaga Journal of Communication, 2024)
This study explores Alfamart's communication strategy for maintaining a positive image amidst the challenges of the digital era and tight business competition. This study's background discusses the negligence of Alfamart store cashiers in providing prices that went viral in 2020. The study focuses on the importance of a strong corporate image as a strategic asset in maintaining consumer loyalty and managing public perception. The purpose of this study is to understand the strategies implemented by Alfamart's Corporate Communication Department, especially in responding to issues that can damage the company's reputation. This study uses a qualitative-descriptive approach with interviews, observations, and documentation. The primary informants are the staff of Alfamart's Corporate Communication Department, supported by store personnel as secondary informants. The data were analyzed using the Image Repair Theory by William L. Benoit and communication strategies by Scott M. Cutlip et al. The results of this study indicate that Alfamart implements communication strategies such as clarification through social media, two-way interaction with consumers, and strengthening positive messages through marketing campaigns and CSR programs. This strategy has effectively improved the company's image since the viral issue. However, this study also found that similar problems recurred in 2024, thus indicating the need for continuous evaluation and improvement in future communication strategies. This study emphasizes the importance of a structured communication strategy and periodic assessment to maintain a positive company image in the digital era.